A short review and selection of soil erosion models (GeoPatterns, 2024)
The article gives a brief review of the related literature concerning soil erosion by surface water flow and provides an outline of several currently available models. They are analyzed in terms of their model structure and spatial and temporal resolution. The focus was on selecting a number of three model approaches that potentially could be applied to the upper and middle sectors of thePrahova River Valley.
Keywords: soil erosion models; RUSLE- 3D; USPED; SPL; Prahova Valley